Development and characterization of red kidney bean (Phaseolus vulgaris L.) paste. - Pineda, Pearl Anne S. (2016.)
This study was performed in a laboratory scale with three replications of each formulation in the production of Red Kidney bean paste. Three Red Kidney bean paste was formulated by combining Red Kidney bean with cornstarch at 3 levels such as (Red Kidney bean: cornstarch): F1 (70:30), F2 (80:20) and F3 (90:10). F3 (90:10) was the most preferred formulation of the Red Kidney bean paste. The MPKBP was then subjected to General Acceptability which obtained a ?like very much? rating with a median source of ?8?. Descriptive Test was also used to measure the sensorial attributes of the MPKBP. MPKBP was characterized through proximate analysis and determined its anthocyanin and radical scavenging activity. The proximate composition of MPKBP such as moisture content, crude protein, crude fat, ash, crude fiber, and carbohydrate were found to be 48.0%, 5.00%, 8.86%, 2.21%, 2.13% and 33.9% respectively. The anthocyanin content of the MPKBP was 0.837 mg/L and radical scavenging activity of the MPKBP was 14.92%. The anthocyanin content was correlated to the radical scavenging activity of a sample and found out that radical scavenging activity of the Red Kidney bean paste was not purely due to anthocyanin rather it was due to other compounds with anthocyanin components.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Red kidney bean; Phaseolus vulgaris L